The girl bandits of the Warsaw Ghetto : the true story of five courageous young women who sparked an uprising - Hyman, Elizabeth R. (Harper Perennial, 2025)
Tells the untold stories of five extraordinary young Jewish women who played pivotal roles in the Warsaw Ghetto Uprising. From fighters and couriers to rescuers and smugglers, these women demonstrated courage, ingenuity, and resilience in the face of Nazi oppression. By highlighting their heroism, Hyman brings long-overdue recognition to the women of the Jewish resistance and their indomitable spirit during one of history's darkest times.